2015
DOI: 10.1063/1.4931038
|View full text |Cite
|
Sign up to set email alerts
|

Protective capping of topological surface states of intrinsically insulating Bi2Te3

Abstract: We have identified epitaxially grown elemental Te as a capping material that is suited to protect the topological surface states of intrinsically insulating Bi 2 Te 3 . By using angle-resolved photoemission, we were able to show that the Te overlayer leaves the dispersive bands of the surface states intact and that it does not alter the chemical potential of the Bi 2 Te 3 thin film. From in-situ four-point contact measurements, we observed that the conductivity of the capped film is still mainly determined by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…On the other hand, the Te 3d 5/2 and Te 3d 3/2 peaks are slightly influenced by this capping procedure since their lineshape peak positions are shifted by ∼ 0.8 eV toward higher binding energies upon the deposition of the Te overlayer. This shoulder has been observed previously and was attributed to elemental Te 11,24 . The XPS data on Te capped film are in agreement with recent in-situ ARPES and four-point probe conductivity data on Bi 2 Te 3 films 11 , which revealed that the surface states of the pristine Bi 2 Te 3 samples are not affected by the Te capping, thus suggesting the Te capping method does not cause a doping of the sample.…”
Section: In-situ Surface Characterizationsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the Te 3d 5/2 and Te 3d 3/2 peaks are slightly influenced by this capping procedure since their lineshape peak positions are shifted by ∼ 0.8 eV toward higher binding energies upon the deposition of the Te overlayer. This shoulder has been observed previously and was attributed to elemental Te 11,24 . The XPS data on Te capped film are in agreement with recent in-situ ARPES and four-point probe conductivity data on Bi 2 Te 3 films 11 , which revealed that the surface states of the pristine Bi 2 Te 3 samples are not affected by the Te capping, thus suggesting the Te capping method does not cause a doping of the sample.…”
Section: In-situ Surface Characterizationsupporting
confidence: 82%
“…Combining different surface-sensitive in-situ characterization tech-niques, we demonstrated that the surface morphology and electronic band structure of Bi 2 Te 3 are not affected by in-vacuo storage and exposure to oxygen, whereas major changes are observed when films are exposed to ambient conditions. Independently, combined in-situ fourpoint probe conductivity and angle resolved photoemission spectroscopy experiments revealed the bulk insulating properties of Bi 2 Te 3 thin films with metallic surface states 10,11 . In the work of Hoefer et al 10 , the authors also demonstrated that short exposure to air causes the bulk conduction band to be filled with electrons and the conductivity is no longer determined by the surface states alone.…”
Section: Introductionmentioning
confidence: 97%
“…Before taking the samples out of the growth chamber they were capped with a 3 or 5 nm thick Te protective layer. 25 A list of all the studied samples with relevant details is given in LE-µSR experiments were performed at the µE4 beam line of the Paul Scherrer Institute. 26 The samples were glued using silver paint onto Ni-coated sample plates and mounted on the cold finger of a helium flow cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Refinements of this technique have shown that it is possible to restore pristine surfaces after thermal removal of sputtered Se capping on Bi 2 Se 3 , which was exposed to air for a few hours 20 or thermal desorption of ultra-thin Te capping on Bi 2 Te 3 films after exposition to air for 5 min. 21 A third technique applied to layered van der Waals materials consists of cleaving thin films (thicker than 50 nm) inside the UHV chamber to remove the oxidized surface, exposing a new fresh surface to perform the aimed analysis. 17 However, this procedure changes both film thickness and surface morphology, leading to uncontrollable parameters for surface characterization.…”
mentioning
confidence: 99%